(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Mercury (Hg) is a toxic element released into the environment mainly by anthropic activities. Consequently, the improvement for Hg determination in environmental samples is of great interest. Instrumental Neutron Activation Analysis (INAA) is considered an adequate method to determine several elements. However, Hg determination by INAA is often hampered by its volatility, which causes losses. The aim of this study was to establish adequate irradiation conditions for Hg determination in environmental samples by INAA. The following parameters were evaluated: irradiation time, container for irradiation and spectral gamma ray interferences. For the study, aliquots of certified reference materials (CRMs) and tree bark samples were irradiated together with Hg synthetic standard at the IEA-R1 nuclear research reactor. Gamma ray activities of 197Hg and 203Hg were measured in a spectrometer coupled to a HGe detector. Obtained results indicated that polyethylene capsules or envelopes can be used as container for sample irradiation and the Hg impurities in these containers were negligible. Irradiation time of one hour was adequate for Hg determination and in long irradiations of 8 h problems of spectral interference of 198Au and 75Se were observed. In addition, Hg loss during the irradiation of 1 h and after irradiation was not observed. Quality control of Hg results, obtained in the CRMs analyses using one hour of irradiation, indicated good precision and accuracy with HORRAT < 2 and |Z score| < 2. The experimental conditions established in this study were applied to tree bark samples. Detection limits in these analyses were between 0.14 and 1.9 µg g-1.